(untitled) (Ágora Journal, 2021)
This article examines the trajectory of Cleonice Assumpção Alakija, who was one of the first black doctors in Salvador. In this text, the reader will have the opportunity to know what was the importance that the doctor’s family had for his academic formation, her passage through the Faculty of Medicine of Bahia, and some information about her life after graduation. The central issue of the narrative was to relate the doctor’s trajectory with the historical context in which she lived, with its challenges and possibilities.